In vivo identification of arteries and veins using two‐photon excitation elastin autofluorescence. Issue 1 (29th August 2019) - Li, Hui; Yan, Meng; Yu, Jia; Xu, Qiang; Xia, Xianyuan; Liao, Jiuling; Zheng, Wei
Abstract: Distinguishing arteries from veins in vivo has a great significance in clinical practices and preclinical studies. Optical imaging methods such as two‐photon microscopy can provide high‐resolution morphological information of tissue and are therefore extremely suitable for imaging small blood vessels. However, few optical imaging methods allow in vivo identification of arteries and veins merely utilizing the autofluorescence signal of blood vessels. In this report, we found the arterial wall generates a remarkably stronger two‐photon excitation autofluorescence (TPEA) signal compared with the venous wall based on BALB/c mice. According to histological analysis and fluorescence characteristic measurement, the contrast signal is confirmed to be from elastin fibers. Employing this unique feature, we propose an objective and effective artery–vein separation strategy that considers the presence of the elastin‐TPEA border as the indicator of arteries. Using this strategy, the arterial and venous networks of the dorsal skin and cerebral cortex of BALB/c mice are demonstrated to be excellently mapped and accurately separated in vivo without depending on any exogenous contrast agent, empirical knowledge, and algorithm. This study may provide a novel technique for mapping arterial and venous networks for anatomic research as well as an extra aid to basic researches on the mechanism, diagnosis, and treatment of blood vessel‐related diseases. Abstract : In vivo identification of arteries and veins is of great value for clinical practices and preclinical studies. We propose a simple and objective artery–vein separation strategy that considers the presence of the elastin‐TPEA border as the indicator of arteries. According to this strategy, the arterial and venous networks of mouse skin and cerebral cortex are excellently mapped and accurately separated in vivo without depending on any exogenous contrast agent, empirical knowledge, and algorithm.